Analisis Kualitas Layanan Website Bukalapak Terhadap Kepuasan Pengguna Menggunakan E-S-QUAL - Cindy Farah Safira; Ari Kusyanti; Himawat Aryadita (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
E-commerce or short for electronic commerce is a business transaction that occurs in electronic networks such as internet. E-commerce should pay attention to the quality of service, because the quality of an e-commerce is very influential on the number of customers who access and decide to shop using e-commerce. Bukalapak is one of the fastest growing e-commerce development in Indonesia. In 2015, Bukalapak website ranks first in e-commerce in Indonesia. But in 2017, Bukalapak website has decreased one rating. It shows that the importance of user satisfaction in affecting the service quality so that Bukalapak website ranking increased. This research uses E-S-QUAL with Multiple Linear Regression analysis. The results show that Efficiency, System Availability, Fulfillment, Privacy, and Responsiveness have a significant influence on Bukalapak website user satisfaction. However, the Compensation and Contact variables, have no effect. Efficiency variable becomes the most important factor in influencing the satisfaction of the Bukalapak website users. This proves that ease and quick access to Bukalapak's website provides a high level of satisfaction as it meets the expectations of users.